Polygoni Multiflori Radix Praeparata polysaccharides enhance gut health and mitigate ischemic stroke by regulating SCFA and amino acid metabolism in gut microbiota - Ruan, Lingyu; Wang, Zhennan; Zheng, Mengyun; Zheng, Qi; Qing, Qing; Lin, Hongyan; Tao, Yuheng; Wang, Liqun; Wang, Junsong; Ge, Wenhao (Frontiers in Pharmacology, 2025)
Background and purposeIschemic stroke (IS) is the most common type of stroke, known for its high rates of morbidity, disability, mortality, and recurrence. Polygoni Multiflori Radix Praeparata (PM), a traditional Chinese medicinal tonic, is frequently used for treating IS. Its polysaccharides (PMP) are acknowledged for their hepatoprotective, immunomodulatory, and neuroprotective properties. However, the effectiveness and mechanisms of PMP remain inadequately understood. This study seeks to evaluate the impact of PMP on IS and clarify the potential mechanisms involved.MethodsPMP was obtained by water extraction, alcohol precipitation, Sevage deproteinization, and dialysis. Its molecular weight, monosaccharide composition, and FT-IR spectrum were characterized. IS was established by middle cerebral artery occlusion/reperfusion (MCAO/R) in male SD rats. Neurological assessment, histopathology, and protein factors detection assessed PMP’s effectiveness. Further, 1H NMR based metabolomics and 16S rRNA gene sequencing examined gut microbiota metabolites and profiles, respectively, in order to elucidate the underlying mechanisms from the perspective of the gut-brain axis.ResultsPMP significantly improved the neurologic functions and reduced the cerebral infarction volume in MCAO/R rats. Cerebral ischemia/reperfusion (I/R) injured brain and also affected intestine, leading to gut barrier disruption. PMP could lower the levels of inflammatory cytokines, such as TNF-α and IL-1β, and boost tight junction protein both in brain and intestinal tissues. Metabolomic analysis shows PMP raised intestinal levels of SCFAs (butyrate, propionate) and beneficial amino acids, thus improving disrupted carbohydrate and amino acid metabolism. 16S rRNA gene sequencing revealed that the abundance of Bifidobacterium, Muribaculaceae, and Lactobacillus was reversed after PMP intervention. The family Bacteroidaceae and the genus Bacteroides correlated positively with amino acids, and might contributed to the SCFAs production. While the family Peptostreptococcaceae and the genus Romboutsia correlated negatively with SCFAs, might related to the poor prognosis of IS.ConclusionPMP markedly enhanced SCFAs and amino acid metabolism, as well as the proliferation of beneficial gut microbiota, thereby promoting intestinal health and barrier integrity, and thus relieving MCAO/R induced I/R injury both in brain and intestine. Our study substantiates the potential of PMP as a prebiotic health supplement in clinical settings for the prevention and treatment of IS.